Influencing factors of coking coal dust explosion pressure and flame and effect of inert dust on its explosion suppression - Tianqi Liu; Xuan Zhao; Weiye Tian; Ruiheng Jia; Ning Wang; Zhixin Cai (Scientific Reports, 2022)
Abstract Coking coal is a precious resource in the world and an important raw material for the production of steel, but it is easy to cause explosion accidents in the process of coking coal mining, which is very detrimental to safe production. In order to reveal the influencing factors of coking coal dust explosion intensity and the suppression effect of inert dust on coking coal dust explosion, an experimental study was carried out in this paper. The results show that the particle size and the mass concentration of coal dust have a great influence on the explosion pressure and flame. By analyzing the suppression effects of NaCl, KCl, and NH4H2PO4 on coking coal dust explosion, it is got that NH4H2PO4 has the best explosion suppression effect. When the mass percentage of NH4H2PO4 mixed into coking coal dust increases to 60%, the maximum explosion pressure decreases by 0.47 MPa, and the maximum flame length decreases by 0.50 m. As the particle size of NH4H2PO4 decreases, the explosion intensity continue to decrease. When the particle size of NH4H2PO4 is 0 ~ 25 μm, and the mass percentage of NH4H2PO4 mixed into coking coal dust is 50%, the explosion doesn’t occur anymore.